Ion-Beam-Induced Epitaxial Recrystallization Method and Its Recent Applications - Lang, Rossano; Menezes, Alan de; Santos, Adenilson dos; Reboh, Shay; Meneses, Eliermes; Amaral, Livio; Cardoso, Lisandro (IntechOpen, 2012)
None